Testicular Nitric Oxide and Thiobarbituric Acid Reactive Substances Levels in Obstructive Azoospermia: A Possible Role in Pathophysiology of Infertility (Mediators of Inflammation)
<emph>Objective</emph>. The aim of the study is to evaluate the levels of nitrite/nitrate and thiobarbituric acid reactive substances (TBARS) and their relationship with seminal parameters in experimental obstructive azoospermic rats to explain the possible mechanism of impaired sperm quality in obstructive azoospermia. <emph>Methods</emph> . A total of 10 male Spraque-Dawley rats underwent bilateral vas resection and ligation (Group-1=vasectomy group). The findings were compared with control group ( Group-2=sham group,n=10). Animals were sacrificed 8 weeks after surgery. Testes were removed and used for the evaluation of nitrate/nitrite and TBARS levels and for histology. Epididymal-aspirated seminal plasma was used for semen count and morphological analysis according to the Kruger criteria. <emph>Results</emph>. Testicular tissue nitrate/nitrite and TBARS levels were 35.7±3.1μ mol/g protein and 3.7±0.1 nmol/g protein in Group-1, and 19.3±0.7 μ mol/g protein and 3.1±0.1 nmol/g protein in Group-2, respectively. Both parameters showed statistical differences between the two groups. Testicular tissue nitrate/nitrite and TBARS levels showed negative and statistically significant correlations with sperm motility and morphology. <emph>Conclusions</emph>. The present study showed that testicular nitrate/nitrite and TBARS levels were increased in obstructive azoospermia. For that reason, we concluded that antioxidant treatment can be recommended to patients before sperm extraction for artificial reproduction due to obstructive infertility after vasectomy reversal.